Simulation of human behaviour in adherence to preventive health programmes A methodological proposal and an example of its application - Pereira, A.; Laureano, Raul M. S.; Neto, F. (CISTI'2024 - 19th Iberian Conference on Information Systems and Technologies, 2024)
In this paper, the authors present an approach to the development of simulation models that consider heath related individual behavior and the relations and patterns that explain it, based on our personal experience and in the published works of other authors with proven results in this field of research. The authors demonstrate this approach using a real example of a computational simulation model focused on understanding the behavioral drivers behind the adherence to diabetic retinopathy screenings and the potential impact of different interventions. The model uses real data from 271,867 invitations for screening in the Portuguese Northern Regional Health Administration. The results obtained bear close resemblance to real world values, both in the training and in the test sets, which attests to the validity of the model for the study of this problem and its usefulness as a predictive tool for public health planning.